Metode Learning Tournament Untuk Meningkatkan Kreativitas Dan Hasil Belajar Siswa Kelas III Dalam Pembelajaran Pendidikan Agama Islam Di SDN 17 Batang Anai Kabupaten Padang Pariaman - Nurlaili Nurlaili (Jurnal Konseling dan Pendidikan, 2016)
This research is based on fact that creativity and learning output of religion subject of students grade III in SDN 17 Batang Anai are still low. This research is aimed to improve creativity and learning output of students grade III SDN 17 Batang Anai by implementing Learning Tournament method. This is a class action research that consists of two cycles including four steps: planning, action, observation, and reflection. Data of research were obtained through observation, note, and test. Obtained data were analyzed quantitatively and qualitatively. In cycle I, percentage of student’s creativity score is 28.48%and become 78.33% in cycle II. Meanwhile, percentage of student’s learning output score in cycle I is 50.00% and become 83.33% in cycle II. Hence, it can be concluded that Learning Tournament method can improve creativity and learning output of students grade III SDN 17 Batang Anai.